EFEKTIFITAS SLOGAN GERAKAN CINTA ZAKAT MELALUI PENDISTRIBUSIAN DAN PENDAYAGUNAAN ZAKAT PRODUKTIF PADA BAZNAS KOTA GORONTALO - Norma Ningsih Bugi; Muhammad Ardi (MUTAWAZIN (Jurnal Ekonomi Syariah), 2021)
The purpose of this study is to see the effectiveness of the movement of zakat love in Baznas in gorontalo city. Because this is a new program launched by president Jokowi. The author uses qualitative descriptive method to express the problem in depth and thoroughly, which is useful to provide information, facts and data about the program of zakat love movement in BAZNAS Gorontalo city for underprivileged people in Gorontalo city, by conducting interviews directly to baznas employees of Gorontalo city and people who receive zakat love movement funds. The results of the research conducted the results that the target of the program conducted by BAZNAS Gorontalo city is appropriate. This is evidenced by the selection process conducted by baznas to the candidate mustahiknya. The selection is useful to see if the candidates who are helped mustahik really poor and worthy to be given help. This is done to avoid any assistance that is not on target provided by BAZNAS. So that the help of productive zakat funds can be given to those who deserve help.